Optimizing the Role of Adolescents in Preventing Early Marriage Through Advocacy of Reproductive Health Rights. - Fitriani, Fitriani; Husnah, Ridni; Fariningsih, Erika; Kartika, Adila Citra (Edumedia Solution, 2025)
Wedding age early Still become challenge serious in Indonesia because its complex impact to health , education and welfare social teenagers. Activities devotion public This aiming For optimize role teenager in prevention wedding age early through advocacy rights health reproduction. Activities implemented at SMAN 7 Batam in May 2025, with involving 32 teenagers age 14–18 years. The method used covering education interactive, discussion group, training advocacy , as well as simulation and formation group peers. Evaluation is carried out through pre-test and post-test, observation participatory, as well as interview. The results show improvement significant to knowledge teenager related health reproduction (62.5%), impact wedding age early (71.87%), rights adolescents (68.75%), and advocacy strategies (81.25%). In general qualitative, teenagers show better understanding comprehensive and attitude critical to practice wedding age early. They also showed initiative For share information and form group Advocacy. Activities This prove that teenager own potential big as agent change in effort prevention wedding age early, and advocacy rights health reproduction is an effective strategy in empowerment teenager For create change positive social.